Drosophila Ahcy is a redox sensor that modulates gene expression to protect against light stress–induced retinal degeneration - Sarah C. Stanhope; Kratika Singhal; Nicolás M. Morato; Yunfei Feng; Gaoya Meng; Makayla N. Marlin; Claudia C. Kotanko; Madolyn M. Jarrett; Andrew D. Mesecar; R. Graham Cooks; Vikki M. Weake (Proceedings of the National Academy of Sciences, 2025)
One-carbon metabolism influences gene expression by providing methyl units for DNA, RNA, and histone methylation. Robust methylation requires rapid hydrolysis of the methylation by-product S -adenosylhomocysteine (SAH) by S -adenosylhomocysteinase (Ahcy). Ahcy is essential for maintaining methylation potential; however, the mechanisms governing its enzymatic activity, particularly in response to cellular stress, remain largely uncharacterized. Here, we show Ahcy is a redox-sensitive enzyme that is inhibited by oxidation of a conserved cysteine, C195, in vitro resulting in elevated SAH levels upon oxidative stress in vivo. We leveraged High-Throughput Desorption Electrospray Ionization Mass Spectrometry to directly quantify Ahcy enzymatic activity and observed that H 2 O 2 -induced oxidation significantly reduced its catalytic efficiency. Notably, while C195 is essential for enzymatic activity in Drosophila melanogaster and humans, this residue is not conserved in Caenorhabditis elegans Ahcy that is also insensitive to H 2 O 2 . Structural analysis revealed that C195 is positioned near NAD + in the active site, close to a second cysteine residue that is also lacking in C. elegans Ahcy. Ahcy oxidation is neuroprotective in a Drosophila light stress model that increases oxidative stress. Moreover, Ahcy knockdown suppresses light stress–induced gene expression changes in photoreceptors, although this response is uncoupled from changes in H3K4me3 and H3K27me3 levels, which were previously reported to alter in response to Ahcy knockdown in cultured cells. Thus, the one-carbon metabolism enzyme Ahcy senses changes in cellular redox homeostasis through a conserved cysteine residue that alters its activity, enabling rapid changes in gene expression that enable a neuroprotective response.